2020
DOI: 10.1177/0950422220903618
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the enterprising tendencies of Arab female undergraduate engineering students in the Sultanate of Oman

Abstract: This study assesses the enterprising characteristics of first-year undergraduate Omani female chemical engineering students in Muscat, Oman. Pre and post surveys were conducted with 27 respondents from an entrepreneurship boot camp module mandated by the Oman Ministry of Higher Education. The variables, measured on a 10-point Likert scale, included need for achievement, need for autonomy, creativity, risk-taking, and locus of control. Statistical analysis was performed on the integrated data to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Although Ryan et al (2011) found that UAE-national females exhibited higher levels of autonomy compared to males, we found a lower result for the need for autonomy and achievement for female students. Our findings are similar to the research outcomes of van Der Lingen and van Niekerk (2015) and Yasin et al (2020) and can be associated with the cultural foundations of the MENA region, and the Arab world, where females are underrepresented in professional and educational societies (Moult and Anderson, 2005;Rhoudi-Fahimi and Moghadam, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Although Ryan et al (2011) found that UAE-national females exhibited higher levels of autonomy compared to males, we found a lower result for the need for autonomy and achievement for female students. Our findings are similar to the research outcomes of van Der Lingen and van Niekerk (2015) and Yasin et al (2020) and can be associated with the cultural foundations of the MENA region, and the Arab world, where females are underrepresented in professional and educational societies (Moult and Anderson, 2005;Rhoudi-Fahimi and Moghadam, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Empirical evidence reported that male students with a high need for achievement tend to choose a career related to entrepreneurial nature (McClelland, 1965). A similar finding was also reported among female students in terms of its effect on entrepreneurial intention in Saudi Arabia (Bhatti et al, 2021) and entrepreneurial abilities in Oman (Yasin et al, 2020). Nevertheless, the literature is relatively scarce on the relationship between the need for achievement, an actual entrepreneurial venture and the subsequent entrepreneurial performance among women entrepreneurs.…”
Section: Theoretical Foundations and Hypotheses Developmentmentioning
confidence: 61%
“…Also, in the past couple of years, during the COVID-19 pandemic, extensive research has been carried out and published regarding the impact of entrepreneurship education in HEIs. Entrepreneurship education in GCC region itself has undergone a massive evolution, from just a course offered to all students to graduate/postgraduate degree specializations (Elnadi et al , 2020; Yasin et al , 2020). Furthermore, nonacademic initiatives regarding entrepreneurial mindset development have witnessed an overall increase.…”
Section: Analysis and Findingsmentioning
confidence: 99%